Peran Good Corporate Governance dalam Meningkatkan Kepercayaan Anggota BMT NU Balen Bojonegoro - lora, erma (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2025)
The development of sharia economy in Indonesia shows a significant trend, one of which is marked by the presence of microfinance institutions such as Baitul Maal wat Tamwil. As an institution based on community and Islamic values, the sustainability of BMT is greatly influenced by the trust of its members. This trust is closely related to the implementation of the principles of GCG, which include transparency, accountability, responsibility, independence, and fairness. This study aims to analyze how the implementation of GCG principles in BMT NU Balen, and to what extent it has an impact on the level of member trust. The method used is a descriptive qualitative approach, with data collection techniques in the form of literature studies, semi-structured interviews, and documentation. The results of the study show that although not yet documented in the form of written guidelines, GCG principles have been implemented substantially in the operational activities of BMT NU Balen. Practices such as information transparency, routine performance reporting, and social services based on the values ​​of justice and responsibility have been shown to increase member loyalty and participation. Member trust is reflected in the high number of repeat transactions and the entry of new members through recommendations. This study concludes that consistent GCG implementation can strengthen the trust and sustainability of the institution. In the future, it is important for BMT to formulate formal GCG guidelines and improve sharia governance literacy for members. Keywords: Sharia governance; Good Corporate Governance; member trust; sharia cooperative; BMT NU